Maintenance cognitive stimulation therapy for dementia: single-blind, multicentre, pragmatic randomised controlled trial. (June 2014) - Orrell, Martin; Aguirre, Elisa; Spector, Aimee; Hoare, Zoe; Woods, Robert T.; Streater, Amy; Donovan, Helen; Hoe, Juanita; Knapp, Martin; Whitaker, Christopher; Russell, Ian
Abstract : Background: There is good evidence for the benefits of short-term cognitive stimulation therapy for dementia but little is known about possible long-term effects. Aims: To evaluate the effectiveness of maintenance cognitive stimulation therapy (CST) for people with dementia in a single-blind, pragmatic randomised controlled trial including a substudy with participants taking acetylcholinesterase inhibitors (AChEIs). Method: The participants were 236 people with dementia from 9 care homes and 9 community services. Prior to randomisation all participants received the 7-week, 14-session CST programme. The intervention group received the weekly maintenance CST group programme for 24 weeks. The control group received usual care. Primary outcomes were cognition and quality of life (clinical trial registration: ISRCTN26286067). Results: For the intervention group at the 6-month primary end-point there were significant benefits for self-rated quality of life (Quality of Life in Alzheimer's Disease (QoL-AD) P = 0.03). At 3 months there were improvements for proxy-rated quality of life (QoL-AD P = 0.01, Dementia Quality of Life scale (DEMQOL) P = 0.03) and activities of daily living ( P = 0.04). The intervention subgroup taking AChEIs showed cognitive benefits (on the Mini-Mental State Examination) at 3 ( P = 0.03) and 6 months ( P = 0.03). Conclusions: Continuing CST improves quality of life; and improves cognition for those taking AChEIs.